Cross Border Collaboration: A Network Analysis of the Bilateral Collaborative Projects in the Case of Greece and Bulgaria - Ioannis Katsikis; Garyfallos Fragidis; Dimitrios Paschaloudis (European Regional Science Association (ERSA), 2012)
Although neighboring countries and both members of the EU, Greece and Bulgaria have very different social and economic environments in which entrepreneurial activities take place. At the same time, collaborative activities and research on economic and social cohesion and development between the organizations of Greece and Bulgaria is only minimal. In this empirical paper, we study the collaborative projects initiated by the organizations of the countries in order to understand the collaborative status of the two nations, their priorities and targets. Thus, we analyse the 34 research project proposals funded by the European Territorial Cooperation Program Greece-Bulgaria 2007-2013, (Interreg IV). Interreg IV is an EU initiative which aims to stimulate interregional cooperation in the EU between the years 2007-13. It is financed under the European Regional Development Fund (ERDF). This phase of the Interreg initiative is designed to strengthen economic and social cohesion throughout the EU, by fostering the balanced development of the continent through cross-border, transnational and interregional cooperation. Special emphasis has been placed on integrating remote regions and those which share external borders with the candidate countries. The eligible areas of the programme in the case of Greece and Bulgaria, contains seven Regional Units (former Prefectures) on the Greek side (Evros, Kavala, Xanthi, Rodopi, Drama, Thessaloniki and Serres) and four Districts on the Bulgarian side (Blagoevgrad, Smolyan, Kardjali, Haskovo), covering an area of 40.202 km2 and 2.812.236 inhabitants. In our work we performe a network analysis in order to examine data relevant to the projects priority axis, the number of the partners involved, the type of the partners and their nationality. Our analysis provides interesting results for the specific organizations, the conditions and the targets of the projects for which they choose to collaborate under the specific EU funded scheme. Furthermore, our research sheds light on the competences and the competitive advantages for the partners selection process. Based on those results, our paper concludes by providing insights on the regional and organizational strategies for the internationalization and the development of bilateral collaboration between the organizations of the two countries that could contribute positively in responding to the current economic crisis in Greece.
Keywords: L26; F23; F21; 330; cross border cooperation; international entrepreneurship; Greece; Bulgaria